3D Chemical Shift‐Encoded MRI for Volume and Composition Quantification of Abdominal Adipose Tissue During an Overfeeding Protocol in Healthy Volunteers. Issue 6 (16th October 2018) - Nemeth, Angeline; Segrestin, Bérénice; Leporq, Benjamin; Seyssel, Kevin; Faraz, Khuram; Sauvinet, Valérie; Disse, Emmanuel; Valette, Pierre‐Jean; Laville, Martine; Ratiney, Hélène; Beuf, Olivier
Abstract : Background: Overweight and obesity are major worldwide health concerns characterized by an abnormal accumulation of fat in adipose tissue (AT) and liver. Purpose: To evaluate the volume and the fatty acid (FA) composition of the subcutaneous adipose tissue (SAT) and the visceral adipose tissue (VAT) and the fat content in the liver from 3D chemical‐shift‐encoded (CSE)‐MRI acquisition, before and after a 31‐day overfeeding protocol. Study Type: Prospective and longitudinal study. Subjects: Twenty‐one nonobese healthy male volunteers. Field Strength/Sequence: A 3D spoiled‐gradient multiple echo sequence and STEAM sequence were performed at 3T. Assessment: AT volume was automatically segmented on CSE‐MRI between L2 to L4 lumbar vertebrae and compared to the dual‐energy X‐ray absorptiometry (DEXA) measurement. CSE‐MRI and MR spectroscopy (MRS) data were analyzed to assess the proton density fat fraction (PDFF) in the liver and the FA composition in SAT and VAT. Gas chromatography‐mass spectrometry (GC‐MS) analyses were performed on 13 SAT samples as a FA composition countermeasure. Statistical Tests: Paired t ‐test, Pearson's correlation coefficient, and Bland–Altman plots were used to compare measurements. Results: SAT and VAT volumes significantly increased ( P  < 0.001). CSE‐MRI and DEXA measurements were strongly correlated ( r  = 0.98, P  < 0.001). PDFF significantly increased in the liver (+1.35, P  = 0.002 for CSE‐MRI,  + 1.74, P  = 0.002 for MRS). FA composition of SAT and VAT appeared to be consistent between localized‐MRS and CSE‐MRI (on whole segmented volume) measurements. A significant difference between SAT and VAT FA composition was found ( P  < 0.001 for CSE‐MRI, P  = 0.001 for MRS). MRS and CSE‐MRI measurements of the FA composition were correlated with the GC‐MS results (for ndb : rMRS/GC‐MS  = 0.83 P  < 0.001, rCSE‐MRI/GC‐MS  = 0.84, P  = 0.001; for nmidb : rMRS/GC‐MS  = 0.74, P  = 0.006, rCSE‐MRI/GC‐MS  = 0.66, P  = 0.020) Data Conclusion: The follow‐up of liver PDFF, volume, and FA composition of AT during an overfeeding diet was demonstrated through different methods. The CSE‐MRI sequence associated with a dedicated postprocessing was found reliable for such quantification. Level of Evidence : 1 Technical Efficacy : Stage 2 J. Magn. Reson. Imaging 2019;49:1587–1599.